ANALISIS EFEKTIVITAS PEMBERIAN TAMBAHAN PENGHASILAN PEGAWAI (TPP) TERHADAP KINERJA PEGAWAI DI KANTOR DINAS PENDIDIKANKOTA GUNUNGSITOLI - Pandu Cahaya Dwinayanti Laowo; Odaligoziduhu Halawa; Sukaaro Waruwu; Palindungan Lahagu (Jurnal Publikasi Manajemen Informatika, 2026)
This study aims to analyze the effectiveness of Employee Additional Income (TPP) on the performance of civil servants at the Education Office of Gunungsitoli City. The research employed a descriptive qualitative approach with data collection techniques including observation, interviews, and documentation. The research informants consisted of structural officials and staff who were considered to have adequate understanding and direct involvement in the implementation of TPP. The findings indicate that the implementation of TPP has been carried out based on existing regulations and procedures. Nevertheless, several challenges remain in practice. In general, TPP has contributed to improving employee attendance discipline and administrative compliance. However, its impact on enhancing work quality and productivity has not been optimal, as some employees tend to focus merely on fulfilling administrative requirements without demonstrating significant improvements in performance. The inhibiting factors of TPP effectiveness include limited technical understanding in completing the Employee Performance Targets (SKP), weak supervision from superiors, and a passive bureaucratic work culture. Meanwhile, the supporting factors consist of a clear legal framework, the adoption of digitalization systems, and the growing awareness among some employees of the importance of performance.